2006
DOI: 10.1080/00220380600682215
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of genetically modified cotton on South African smallholders: Yield, profit and health effects

Abstract: Results of a large-scale survey of resource-poor smallholder cotton farmers in South Africa over three years conclusively show that adopters of Bt cotton have benefited in terms of higher yields, lower pesticide use, less labour for pesticide application and substantially higher gross margins per hectare. These benefits were clearly related to the technology, and not to preferential adoption by farmers who were already highly efficient. The smallest producers are shown to have benefited from adoption of the Bt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 10 publications
4
54
0
4
Order By: Relevance
“…A commonly cited example of secondary impacts related to changes in labour demand. Some studies pointed out reductions in labour as a cost-saving effect [81,95,100,102], or as a negative effect for those previously employed for spraying [85]. Labour needs were also shown to increase in some cases.…”
Section: The Example Of Bt Cottonmentioning
confidence: 99%
See 3 more Smart Citations
“…A commonly cited example of secondary impacts related to changes in labour demand. Some studies pointed out reductions in labour as a cost-saving effect [81,95,100,102], or as a negative effect for those previously employed for spraying [85]. Labour needs were also shown to increase in some cases.…”
Section: The Example Of Bt Cottonmentioning
confidence: 99%
“…Six studies indicated various positive effects on wellbeing for farmers. Two of these six studies provided first-hand data relating to wellbeing: Bennett et al [81] reported declining hospital visits as a result of reduced pesticide use with Bt cotton in South Africa; Qaim and Kouser [82] found a correlation between improved caloric intake and increased household incomes resulting from the introduction of Bt cotton in India. The remaining four studies reporting positive wellbeing impacts did not measure impacts directly, but relied on farmers reporting such impacts.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
See 2 more Smart Citations
“…Em virtude da complexidade do controle de pragas do algodoeiro, pela existência de inúmeras espécies de pragas-chave, e do uso intensivo de inseticidas para o controle delas, a facilidade de adoção do plantio do algodão Bt tem sido uma das razões de sua utilização por pequenos produtores da África do Sul (Bennett et al, 2006b), México (Traxler & Godoy-Avila, 2004), China (Pray et al, 2004) e Índia (Bennett et al, 2006a). Similarmente, o plantio do algodão no Semiárido do Nordeste é feito basicamente por pequenos produtores, em áreas entre 0,5 e 8 ha (Fontes et al, 2006), e o cultivo do algodão Bt pode ser uma alternativa viável.…”
Section: Introductionunclassified